2016
DOI: 10.3748/wjg.v22.i38.8584
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic disparities in hepatocellular carcinoma treatment and survival in California, 1988-2012

Abstract: AIMTo describe racial/ethnic differences in treatment and survival among liver cancer patients in a population-based cancer registry.METHODSInvasive cases of primary hepatocellular carcinoma, n = 33270, diagnosed between January 1, 1988-December 31, 2012 and reported to the California Cancer Registry were analyzed by race/ethnicity, age, gender, geographical region, socio-economic status, time period of diagnosis, stage, surgical treatment, and survival. Patients were classified into 15 racial/ethnic groups: n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 50 publications
3
60
0
Order By: Relevance
“…Despite this, Wong et al found that from 2009 to 2010, of those potentially eligible for liver transplantation, only 11% of black patients underwent transplantation compared to 20% of white patients. Furthermore, even after adjusting for factors such as tumor stage, age, sex, treatment type, and income, black patients remained significantly more likely than white patients to die from HCC.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, Wong et al found that from 2009 to 2010, of those potentially eligible for liver transplantation, only 11% of black patients underwent transplantation compared to 20% of white patients. Furthermore, even after adjusting for factors such as tumor stage, age, sex, treatment type, and income, black patients remained significantly more likely than white patients to die from HCC.…”
mentioning
confidence: 99%
“…(4) Analyses exploring racial disparities in HCC outcomes have failed to fully explain this disparity on multivariable analysis. (5)(6)(7) Contributing factors that have been explored include late presentation, as black patients have been shown in some cohorts to be more likely to present with advanced tumor burden than white patients. (4) Other analyses have suggested disparities in curative therapies contribute to the racial disparity in HCC mortality.…”
mentioning
confidence: 99%
“…HCC risk factors included waist circumference, BMI, blood pressure, cholesterol, smoking status, diabetes status, and HBV status. While the Hmong are a relatively small Asian group, their distinctiveness as the population experiencing the lowest liver cancer survival rates among all Californians, 8 means that adding a genetic dimension to our prior data on their considerable behavioral risk factors 9 for chronic liver disease expands our insights into contributing etiologies. Having these findings suggest that a high rate of the PNPLA3 SNV should be examined further.…”
Section: Discussionmentioning
confidence: 99%
“…8 Multiple risk factors including viral hepatitis have been identified for HCC pathogenesis. There are different risk factors for NAFLD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation